2020
DOI: 10.1002/adma.202000958
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructures of 2D Molybdenum Dichalcogenide on 2D Nitrogen‐Doped Carbon: Superior Potassium‐Ion Storage and Insight into Potassium Storage Mechanism

Abstract: To meet the requirements of the rapid development of large-scale energy storage systems, "Beyond Li-ion battery (LIB)" systems are attracting more and more attention. [1][2][3][4][5] Among various alkali metals ion batteries, potassium-ion batteries (KIBs) exhibit many advantages for large-scale energy storage system applications including: [6,7] 1) the low manufacturing costs because of the natural abundance of their raw materials; 2) much lower redox potential of K/K + (−2.93 V vs standard hydrogen electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(120 citation statements)
references
References 60 publications
0
120
0
Order By: Relevance
“…Potassium-ion batteries (KIBs) have recently attracted considerable attention for their high energy densities and the abundant availability of potassium as a raw material [1][2][3]. Thus, KIBs are being positioned as an alternative energy storage system to lithium-ion batteries (LIBs), which are currently the dominant power sources for electric vehicles and portable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium-ion batteries (KIBs) have recently attracted considerable attention for their high energy densities and the abundant availability of potassium as a raw material [1][2][3]. Thus, KIBs are being positioned as an alternative energy storage system to lithium-ion batteries (LIBs), which are currently the dominant power sources for electric vehicles and portable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[56,77,81,82] As a result, numerous heterointerfaces and ion reservoirs are formed between the materials, which is beneficial for enhancing the electrochemical kinetics of electrode materials. [83][84][85] In addition, multi-anion electrodes undergo multi-step discharge and charge processes, and higher reversible capacities compared to single-anion counterparts have been observed in many cases. [64,[86][87][88][89][90] Furthermore, it has been reported that the presence of different materials during galvanostatic charge and discharge processes helps alleviate the volume change of the electrode materials because the compounds undergo electrochemical processes at different potentials; materials that are inactive at a certain potential help release the strain received by the other material, and consequently, the cycle life of the electrodes can be prolonged.…”
Section: Theoretical and Experimental Understanding Of Heterostructure Effects And Analytical Tools For Identification Of Components In Hmentioning
confidence: 99%
“…[42] Although research on electrochemical characteristics and energy storage mechanisms of 2D heterostructures is in its early phase, some recently reported 2D heterostructures could deliver superior performances as an electrode of MIBs. [48][49][50] Based on well-known individual characteristics of 2DMs, their heterostructures can be rationally designed for highperformance MIBs electrodes. In this regard, highly conducting 2DMs such as graphene in heterostructures with high energy density TMDs or MXenes enabled a robust electronic and ionic transport as compared to its counterparts.…”
Section: Significance Of 2d Heterostructures For Mibsmentioning
confidence: 99%
“…Rate capability of MoSe 2 , graphene/MoS 2 , and graphene/MoSe 2 and charge/discharge results of graphene/MoSe 2 at different current densities. Reproduced with the permission [48]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%